War and the international trading system in the twentieth century - Hugh Rockoff (Rutgers University, Department of Economics, 2011)
Wars have been the main forces shaping the international trading system in the twentieth century. The early years of the twentieth century were dominated by the international gold standard. But as a result of World War I, this system was replaced by the troubled gold exchange standards of the 1920s and 1930s. As a result of World War II the interwar system was replaced in turn by the Bretton Woods system. And as a result of inflation of the late 1960s, produced in part by America's war in Vietnam, the Bretton Woods system was replaced by the current system of flexible exchange rates. The European monetary union was a response to German reunification and the perceived need to defuse potential conflicts through a high level of economic cooperation.
Keywords: N40; 330; war; finance; globalization; Internationales Währungssystem; Kriegsfolgen; Welt